Parthenium From curse to boon for the farmers - Krishna, Bal; Kumar, Rakesh; Mishra, J S (Indian Farming, 2021)
Parthenium is regarded as worstweeds currently identified and aworldwide weed that causes serioushuman/animal health problems, aswell as agricultural damage andsignificant threat to biodiversity.Plant, on other hand, has someadvantage. Composted partheniumhas a higher nutritional value thanFYM. As a result, compostingParthenium appears to be an effectiveway of using enormous agriculturalweeds.